PEMBELAJARAN SEJARAH YANG TRANSFORMATIF DI ERA DIGITAL - Printina, Brigida Intan; Haryono, Anton; Raharjo, Yoel Kurniawan (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to fulfill one of the tridharma activities of higher education. The form of PkM-PU activity is a Transformative History Learning Workshop in the Digital Era for alumni, History Education students, and History Education School Teachers FKIP USD partners. The first step is to analyze the situation and then plan the activities to be carried out to solve the problem. Then the results of the service are used to develop the ability of service participants and synergies between partner schools and FKIP USD. Therefore, this service is intended to support the professionalism of History teachers to be more competent in conducting historical evaluations through digital media.